Calcium-oligochitosan-pectin microcarrier for colonic drug delivery. (7th February 2020) - Stealey, Samuel; Guo, Xiaoru; Majewski, Rebecca; Dyble, Alexander; Lehman, Kendra; Wedemeyer, Michael; Steeber, Douglas A.; Kaltchev, Matey G.; Chen, Junhong; Zhang, Wujie
Abstract: Pectin-based hydrogel microcarriers have shown promise for drug delivery to the colonic region. Microcarriers must remain stable throughout the upper gastrointestinal tract for effective colonic delivery, an issue that traditional pectin-based microcarriers have faced. The positively-charged natural biopolymer oligochitosan and divalent cation Ca 2+ were used to dually cross-link pectin-based hydrogel microcarriers to improve carrier stability through simulated gastric and intestinal environments. Microcarriers were characterized with Scanning Electron Microscope and Fourier-Transform Infrared analysis. An optical microscope was used to observe the change of microcarrier size and morphology over time in the simulated gastrointestinal environments. Fluorescently-labeled Dextran was used as a model drug for this system. Calcium-Oligochitosan-Pectin microcarriers exhibited relatively small drug release in the upper gastrointestinal regions and were responsive to the high pH and enzymatic activity of simulated colonic environment (over 94% release after 2 h), suggesting great potential for colonic drug delivery. Abstract :